Nuclear localization and nuclear export signals of the human parainfluenza virus matrix protein and their involvement in nuclear transit and virus release - Haas, Micaela (My University, 2018)
Matrix proteins of some viruses within the Paramyxovirinae subfamily transit through the nucleus. This process is needed for virus particle release from cells and is controlled by nuclear localization (NLS) and nuclear export signals (NES). This investigation sought to determine if the matrix protein of one paramyxovirus, human parainfluenza virus 3 (HPIV3) also transits through the nucleus in an NLS/NES-dependent manner. Towards the goal, wild-type matrix protein did localize to the nucleus and localization was influenced by NLS and NES mutations. The NLS mutant, K258A, limited entry of the matrix protein into the nucleus, and the NLS mutant, K258R, and the NES mutant, L106/107A, restricted release of the matrix protein from the nucleus. Regarding production of virus-like-particles, the wild-type M directed VLP formation but the NLS mutations limited formation. Expression of the L106/107A mutant was not detected, so VLP formation ability could not be determined. These results show that HPIV3 M protein nuclear transit was controlled by the NLS and NES signals and the lack of nuclear transit resulted in decreased VLP budding.
Keywords: Extracellular matrix proteins.; Parainfluenza viruses.; Virus diseases.